Reduced-exertion high-intensity interval training (REHIT): a feasible approach for improving health and fitness? - Richard Metcalfe (Applied Physiology, Nutrition, and Metabolism, 2024)
In recent years, research investigating the dose-response to sprint interval training (SIT) has provided evidence that the number and duration of repetitions in a SIT session can be reduced whilst preserving the beneficial health-related adaptations. Together this research has led to the development of protocols involving minimal doses of SIT: regularly performing just two or three 20-30-s all-out sprints in a 10-min training session has been shown to elicit beneficial metabolic and cardiovascular adaptations. These SIT protocols, which we originally termed ‘reduced exertion HIT’ (or REHIT), have the potential to remove many of the common barriers associated with other SIT protocols, as well as with HIT and aerobic exercise. Here, we critically review the evidence on the efficacy, feasibility and acceptability, and effectiveness of REHIT for improving health and fitness.